Music education & law : regulation as an instrument - Heimonen, Marja (Sibelius-Akatemia, 2003)
The aim of this study is to explore the relationship between music education and the law. The principal questions to be addressed are: 1. How do the principles "the right to education" and "freedom in education" function in music education for children and adolescents? Different kinds of music-education systems are explored. The study focuses on the network of Finnish music schools, and on extra-curricular music education for children and adolescents in Sweden, England and Germany. 2. What kind of regulative model would best promote the aims in extra-curricular music education for children and adolescents? Here, regulation as an instrument (means) is examined, and a closer look is taken at the different kinds that are in existence. As a result, a partially open and flexible regulative model of extra-curricular music education for children and adolescents is supported. A balance between positive and negative freedom is the aim of this regulative model; in other words, the model secures the financial resources but at the same time leaves space for human autonomy. It makes holistic aims in music education possible. These aims are similar to the "best interests of the child", which is the most important legal principle in all action concerning children in Finland. Furthermore, this principle, which is formulated in the United Nations Convention on the Rights of the Child, has been ratified over almost all of the world. The conclusion is that the state has to produce the conditions and circumstances for extra-curricular music education for children and adolescents, rather than to regulate the content of music-education activities. This positive role of the law is its principal function regarding regulation governing Finnish music schools. Perspective The approach of this study is interdisciplinary; the research questions are related mainly to music research (especially music education) and law. The intention is to describe the legal and educational issues as they presently are, and in the process of doing this to raise some questions. The perspective is hermeneutic in a holistic way, yet the approach could also be characterised as analytical.
Keywords: musiikkikasvatus; lainsäädäntö; musiikkioppilaitokset; DocMus